Unmasking Greed: Narcissism and 'Love of Money' Drive Financial Statement Fraud - Marsudi Lestariningsih (AKRUAL: JURNAL AKUNTANSI, 2025)
Introduction/Main Objectives: Accountants with narcissistic traits tend to prioritize personal achievement, compared to adherence to ethical standards, and the love of money can also foster positive and negative behaviour. Background Problems:This study aims to test two types of accountant personality, namely narcissism and love of money, on financial report fraud with the control variable intellectual capital. Novelty: Combining two personality types, namely narcissism and love of money, in predicting financial statement fraud. Research Methods: The structural equation modeling-partial least square (SEM-PLS) analysis method was used to test the hypothesis of this study. The questionnaires were distributed to accountants who work as management accountants, public accountants, and public sector accountants and work in the city of Surabaya. Finding/Results:This study concludes that narcissism and love of money have a significant influence on financial statement fraud. In addition, love of money is proven to mediate the relationship between narcissism and financial statement fraud, making it clear that materialistic drives strengthen the negative impact of narcissistic traits. Although intellectual capital is thought to be able to control this relationship, the results of the study show that its influence is still weak in this context. Conclusion: Although intellectual capital reflects a person's abilities and knowledge, this is not enough to prevent bad intentions triggered by narcissistic traits and materialistic drives in committing financial statement fraud.